2002
DOI: 10.7547/87507315-92-3-155
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Hemangioma of the Foot

Abstract: Capillary hemangiomas are benign, vascular lesions of skin and mucous membranes that often occur in infancy and childhood. Capillary hemangiomas are most commonly found in the head and neck region. Capillary hemangiomas that occur in adults and on the lower extremities are uncommon. A clinical case involving surgical treatment of the lesion on an adult foot is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
1
0
7
Order By: Relevance
“…Puede haber decoloración de la piel cuando la masa de tejido blando está muy cerca de la epidermis, esta varía de rojo a marrón o azul a púrpura. 1 La consistencia de los hemangiomas capilares puede variar de suave y esponjosa a una masa dura, y pueden ser fijos o móviles debajo de la epidermis. A menudo se ulceran y sobresalen de la epidermis.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Puede haber decoloración de la piel cuando la masa de tejido blando está muy cerca de la epidermis, esta varía de rojo a marrón o azul a púrpura. 1 La consistencia de los hemangiomas capilares puede variar de suave y esponjosa a una masa dura, y pueden ser fijos o móviles debajo de la epidermis. A menudo se ulceran y sobresalen de la epidermis.…”
Section: Discussionunclassified
“…A menudo se ulceran y sobresalen de la epidermis. 1 Las pulsaciones son raras, pero si se detectan, generalmente son adyacentes y se sienten distales a la lesión. En el hemangioma capilar, es común el antecedente de ulceración y sangrado espontáneo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Cione et al in 2002 reported a similar uncommon case of capillary hemangioma involving surgical treatment of the lesion on an adult foot . (3) Uslu M et al in 2014 presented a report of 2 cases of intramuscular hemangioma in children, 1 treated by excision and 1 by percutaneous sclerosis. They stated that Surgical excision, ultrasound or fluoroscopic-guided percutaneous sclerotherapy, and angiographic embolization are all worthy treatment options.…”
Section: Discussionmentioning
confidence: 99%